Redefining closed pores in carbons by solvation structures for enhanced sodium storage - Yibo Zhang; Si-Wei Zhang; Yue Chu; Jun Zhang; Haoyu Xue; Yiran Jia; Tengfei Cao; Dong Qiu; Xiaolong Zou; Da-Wei Wang; Ying Tao; Guiming Zhong; et al. (Nature Communications)
Abstract Closed pores are widely accepted as the critical structure for hard carbon negative electrodes in sodium-ion batteries. However, the lack of a clear definition and design principle of closed pores leads to the undesirable electrochemical performance of hard carbon negative electrodes. Herein, we reveal how the evolution of pore mouth sizes determines the solvation structure and thereby redefine the closed pores. The precise and uniform control of the pore mouth sizes is achieved by using carbon molecular sieves as a model material. We show when the pore mouth is inaccessible to N2 but accessible to CO2 molecular probes, only a portion of solvent shells is removed before entering the pores and contact ion pairs dominate inside pores. When the pore mouth is inaccessible to CO2 molecular probes, namely smaller than 0.35 nm, solvent shells are mostly sieved and dominated anion aggregates produce a thin and inorganic NaF-rich solid electrolyte interphase inside pores. Closed pores are accordingly redefined, and initial coulombic efficiency, cycling and low-temperature performance are largely improved. Furthermore, we show that intrinsic defects inside the redefined closed pores are effectively shielded from the interfacial passivation and contribute to the increased low-potential plateau capacity.